Interaction between process plant operation and cracking furnaces maintenance policy in an ethylene plant - Schulz, Eduardo Nicolás (2000)
This work addresses the problem of the determination of a maintenance policy for cracking furnaces in an ethylene plant, taking into account the interactions between the entire process plant operation and furnace performance. An important recycle stream (ethane from units downstream the furnaces) constitutes part of the feed, so nonlinear models of units from the entire ethylene process have been included in the optimization problem. The resulting model is a mixed integer nonlinear programming problem where integer variables are associated to the number of time cycles that each feed is processed in a furnace.